KOMUNIKASI PEMASARAN VIA FACEBOOK DAN INSTAGRAM DALAM MENINGKATKAN LOYALITAS PELANGGAN ( Studi kasus di Anima Coffee & Chill Kartasura, Sukoharjo) - Buddy Riyanto, Fauzanendra Rahmantyayoga, Maya Sekar Wangi & (Transformasi, 2017)
This research was based on researchers seeing the success of anima coffee & chill seensignificantly within 1 years after the coffee shop be established. The media that used in isfacebook and instagram. The purpose of this research is to describe how marketingcommunications anima coffe & chill via facebook and instagram to improve the customerloyalty. Methods used in research is with the study descriptive qualitative. The result showedthat the activity of marketing communications using instagram can be successfully due to theresponse from customers of any information as a new kind of coffee and promo releasedthrough instagram. But in the use of facebook anima coffee & chill having an smallerresponses than the instagram because that is in facebook post is only connected frominstagram. So update contained in facebook impressed monotonous.Key words: Marketing communications , facebook and instagram , customer loyalty